441 Prognostic impact of clinical and histopathological factors in patients with vulvar flap reconstruction after large vulvar resections for vulvar malignant neoplasms. (18th September 2019) - Leitão, L; Borges de Souza, L; Santos Estrela Terra, S; Ruscitto do Prado, R; Batista Pinheiro Pastore, C; Lopes, A; Lucio Rangel Costa, R
Abstract : Objectives: Analyze the influence of clinical and histopathological factors on the prognosis of patients with vulvar cancer who required surgical flaps reconstruction after large vulvar resections. Methods: From 2001 to 2018, clinical and histopathological features of patients with locally advanced or recurrent vulvar cancer who underwent vulvar flap reconstruction were retrospectively reviewed. Histology, grade, margins, tumor size, lymph node metastasis, comorbidities, previous radiotherapy, recurrent or primary disease, FIGO staging and type of vulvar flap were analyzed. The covariates were evaluated using Cox regression analysis. Results: A total of 157 patients were surgically treated for vulvar cancer, 34 (21%) required vulvar flap reconstruction. Median age was 70 years and 88% (N=31) had squamous cell carcinoma, 20 (58%) were grade 2. Median tumor size was 6, 0 (1, 5–16, 7)cm and all patients had negative margins. Fifteen (44%) were FIGO stage III. Sixteen (47%) had previous radiotherapy and 22 (64%) had recurrent disease. Inguinal lymphadenectomy was performed in 24 (70%) with a lymph node positivity rate of 62% (N=15). Reconstruction was performed mainly with mycutaneous flap (70%; N=24), of these, 15 (44%) with gracilis myocutaneous flap. Twenty five patients (73%) had a recurrence and 16 (47%) deaths of the disease occurred. Estimated overall survival was 72 (CI 95% 35, 9–108) months. Lymph node metastasis was the only factor associated with shorter overall survival 8, 4 (5, 9–23, 65) months (P=0, 018). Conclusions: The presence of lymph nodes metastasis is probably the only factor with impact on the overall survival in patients who required vulvar flap reconstruction.